Concentric bimetallic microjets by electrodeposition - Zhao, Guanjia (2013)
Self-propelled micro and nanosystems are at the forefront of nanotechnology research. Here we describe a method for fabrication of concentric bimetallic microjets via an electrochemical deposition route. These microjet engines consist of an inner platinum layer which is responsible for the catalytic decomposition of H2O2, which subsequently results in bubble-propelled movement. The outer copper layer allows for further functionalization of the microjet engines. These microjet engines are able to move at speeds of 7 bodylengths s-1 at fuel concentrations as low as 0.2% (wt.) of H2O2. The described method obviates the need to use physical vapor deposition (sputtering) and thus is applicable in any low-end equipped laboratory. Such an accessible method is expected to lead to a dramatic increase in the research activity on artificial self-propelled systems.